Julian Schwinger - Jack Ng, Y (London, 1996)
Includes bibliographical references.; In the post-quantum-mechanics era, few physicists, if any, have matched Julian Schwinger in contributions to and influence on the development of physics. A deep and provocative thinker, Schwinger left his indelible mark on all areas of theoretical physics; an eloquent lecturer and immensely successful mentor, he was gentle, intensely private, and known for being â€œmodest about everything except his physicsâ€. This book is a collection of talks in memory of him by some of his contemporaries and his former students: A Klein, F Dyson, B DeWitt, W Kohn, D Saxon, P C Martin, K Johnson, S Deser, R Finkelstein, Y J Ng, H Feshbach, L Brown, S Glashow, K A Milton, and C N Yang. From it, one can get a glimpse of Julian Schwinger, the physicist, the teacher, and the man. Altogether, this book is a must for all physicists, physics students, and others who are interested in great legends